Green Chemistry-Driven Synthesis and Chemical Profiling of Bimetallic Nanoparticles for Anticancer Applications: A Review - Garg, Nancy; Mishra, Varsha; Chauhan, Ritu; Saini, Adesh K.; Kaur, Damandeep; Ramniwas, Seema; Tuli, Hardeep Singh; Saini, Reena V. (Asian Journal of Chemistry, 2025)
Nanotechnology has revolutionized cancer treatment by enabling targeted drug delivery, early detection and personalized therapies. Cancer treatments now include surgery, radiotherapy, hormonal therapy, chemotherapy and the emerging approach of nanotherapy. This new treatment regimen has fewer side effects than other available methods. Biogenic synthesis of nanoparticles is playing a key role as a valuable alternative to chemical and physical routes, providing environmentally friendly products through eco-friendly, low-cost and biocompatible methods. Metal nanoparticles produced via green chemistry using biological sources reduce the risk of side effects and improve the metal’s effectiveness against cancer cells. Green nanoparticles have demonstrated significant potential in inducing cytotoxic effects against a range of cancer cell lines in scientific studies. Because of their synergistic properties, biosynthesized bimetallic nanoparticles incorporating two different metallic elements have emerged as an effective treatment for cancer, outperforming monometallic nanoparticles in terms of biomedical efficacy due to their synergistic properties. Due to the initiation of multiple molecular mechanisms, including apoptosis, necrosis and autophagy, these nanoparticles can penetrate cancer cells and induce their death. Three-dimensional cell culture models, such as spheroids, are used since they can effectively mimic the key characteristics of solid tumors found in humans, for example, their structural organization, cell layering structure, hypoxia and nutrient gradients. Current review highlights the recent advances of the bimetallic nanoparticles synthesized by green chemistry approach with special emphasis on the involvement of phytochemicals in their reduction, stabilization, functionalization processes and cancer killing potential, with a special mention of its efficacy on 3D tumor spheroids model. Similarities and differences with classic synthesis methods are emphasized, showing that the green routes are faster, less energy-consuming and result in less toxic byproducts, which are eco-friendly and bio-medically important. The mechanisms of nanoparticle formation are reviewed here for a better scientific understanding. It goes further by discussing the scalability and applicability of green synthesis with a focus on anticancer potential. In summary, the application of phyto-components for the biosynthesis of nanoparticles holds great promise for the treatment of cancer.